PENGUASAAN HARTA SEBELUM PELAKSANAAN FARAID DI DESA PURBA BARU KECAMATAN LEMBAH SORIK MARAPI KABUPATEN MANDAILING NATAL - Muhammad Ridwan Pasaribu, Fatahuddin Aziz Siregar Muhammad Arsad Nasution (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2020)
This article describes the control of inheritance that has not been divided in a faraid science, because there are some people who postpone the distribution of inheritance according to Islamic law so that often there is unilateral control over inheritance. So the question here is why this happened and what is the community's reasons for this case. To answer this problem, the authors used a field study, namely interviewing directly the parties concerned, especially those in Purba Baru Village, Lembah Sorik Merapi District, Mandailing Natal Regency as a sample. From the interviews the author conducted, we got the answer that this case occurred due to the lack of public knowledge about the science of faraid accompanied by certain reasons so that one-sidedly controlled the inheritance before it was distributed to the heirs, sometimes even selling the inheritance that had not been distributed due to meeting needs daily life, for the cost of a child's wedding reception, or to treat a child.